PERILAKU INFORMASI PARA PENGGALI EMAS TRADISIONAL (GURANDIL) DALAM MELAKUKAN KEGIATAN EKSPLORASI DAN PENGOLAHAN TAMBANG EMAS - Tine Silvana; Yunus Winoto (Universitas Padjadjaran, 2015)
In this study researchers are interested to examine how the behavior of information among the traditional gold mining or